EFFECTS OF SINGLE-DOSE PREEMPTIVE INTRAVENOUS IBUPROFEN ON POSTOPERATIVE PAIN AND OPIOID CONSUMPTION AFTER LAPAROSCOPIC CHOLECYSTECTOMY: A RANDOMIZED CONTROLLED TRIAL (Journal of Medical & Health Sciences Review, 2025)
Background: Laparoscopic cholecystectomy is the modality of choice of symptomatic gallstone disease. Despite the minimal invasiveness of the procedure, postoperative pain is still a daunting problem, which leads to a prolonged use of opioids with associated adverse effects. Administration of NSAIDS before surgery may decrease the postoperative pain and opioid needs. The purpose of this study was to measure the efficacy of a single dose preemptive intravenous ibuprofen regimen at decreasing postoperative pain scores and opioid consumption in patients undergoing laparoscopic cholecystectomy.This was a randomized controlled trial conducted at the Department of Anesthesiology, Jinnah Postgraduate Medical Centre, Karachi on 60 consecutive patients (ASA I–II; 20–60 years of age), eligible for elective laparoscopic cholecystectomy. Thirty patients were randomly assigned in two groups (n=30). Group A got 400 mg of intravenous ibuprofen in 100 mL saline preoperatively and group B received 100 mL of 0.9 percent normal saline (placebo). Standard anaesthetic and surgical protocol was used. At 6, 12 and 24 hours after operation, pain was recorded as a translated version of visual analogue scale (VAS). During the first 24 hours milligrams of opioid consumption (rescue analgesia for VAS>3) was recorded. The data in this study were analyzed with SPSS version 25 by means of t tests or nonparametric tests and significance was p ≤ 0.05.Findings: Overall VAS scores were significantly decreased in Group A at all time points (p